A one health assessment of a “Herding for Health” project at the wildlife-livestock interface in western Ngamiland, Botswana - Quan, Melvyn (University of Pretoria, 2025)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2021.